2018
DOI: 10.1038/s41598-018-33369-z
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-Curcumin-Conjugated DNA Complexes Induces Preferential Prostate Cancer Cells Cytotoxicity and Pause Growth of Bacterial Cells

Abstract: DNA nanotechnology can be used to create intricate DNA structures due to the ability to direct the molecular assembly of nanostructures through a bottom-up approach. Here, we propose nanocarriers composed of both synthetic and natural DNA for drug delivery. The topological, optical characteristics, and interaction studies of Cu2+/Ni2+/Zn2+-curcumin-conjugated DNA complexes were studied using atomic force microscopy (AFM), UV-vis spectroscopy, Fourier transform infrared and mass spectroscopy. The maximum releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…This suggests that the electrophilic nature of curcumin is essential for inhibiting the STAT3 signaling pathway during anticancer therapy [ 33 ]. Metallo-curcumin-conjugated DNA complexes have been constructed using Cu 2+ /Ni 2+ /Zn 2+ metal ions to improve curcumin solubility and enhance DNA-binding ability [ 34 ]. These complexes also showed a better antibacterial activity and significant toxicity to several prostate cancer cell lines [ 34 ] ( Table 1 ).…”
Section: Structure Activity Relationship Of Curcumin and Its Derivmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the electrophilic nature of curcumin is essential for inhibiting the STAT3 signaling pathway during anticancer therapy [ 33 ]. Metallo-curcumin-conjugated DNA complexes have been constructed using Cu 2+ /Ni 2+ /Zn 2+ metal ions to improve curcumin solubility and enhance DNA-binding ability [ 34 ]. These complexes also showed a better antibacterial activity and significant toxicity to several prostate cancer cell lines [ 34 ] ( Table 1 ).…”
Section: Structure Activity Relationship Of Curcumin and Its Derivmentioning
confidence: 99%
“…In addition to curcumin, some of its derivatives have also shown anticancer activity against prostate cancer. Metallo-curcumin conjugated DNA complexes exhibited significant toxicity to prostate cancer cells (PC3, 22Rv1, TRAMP-C1, LNCaP, and DU145) [ 34 ]. Dimethyl curcumin (ASC-J9) has also shown very good activity in enhancing androgen receptor degradation in androgen-dependent prostate cancer [ 20 , 38 ].…”
Section: Anticancer Activity Of Curcuminmentioning
confidence: 99%
“…In this regard, further studies indicated that these complexes triggered tumor cell apoptosis, disturbed mitochondrial membrane potential, and arrested the cell cycle in the S phase via the ROS-dependent cascade. In addition, Vellampatti et al [ 175 ] reported that metallo-CUR-conjugated DNA complexes exerted marked toxic effects toward prostate cancer cells compared to pristine DNA. Furthermore, they evaluated the cellular uptake of these complexes and revealed that DNA complexes containing Cu 2+ /Ni 2+ -CUR showed brighter fluorescence compared to the complexes containing Zn 2+ -CUR.…”
Section: Therapeutic Activity Of Curcumin Nanoformulationsmentioning
confidence: 99%
“…Along with CUR, some of the CUR derivatives have also exhibited anti-cancer effects against prostate cancer. Interestingly, metallo-CUR conjugated DNA complexes exerted marked toxicity to prostate cancer cells (DU145, LNCaP, TRAMP-C1, 22Rv1, and PC3) [ 175 ]. In androgen-dependent prostate cancer, dimethyl CUR(ASC-J9) exhibited good activity in enhancing androgen receptor degradation [ 326 , 327 ].…”
Section: Anticancer Activity Of Curcumin Against Various Types Ofmentioning
confidence: 99%
“…Pabon however, successfully prepared this molecule for the first time in excellent yield in 1964 [ 29 ]. In recent years, curcuminoids and in particular, curcumin have attracted a lot of attention due to their pharmacological activity and biological effects, tested directly or chelated to metal centres [ 30 , 31 , 32 , 33 ]. Furthermore, curcumin has been deeply studied for its antioxidant properties in molecular biology research [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%